The interaction of HVEM generated point-defects with dislocations in Fe-Ni-Cr alloys - King, S; King, Simon (1990)
﻿ The climb of dissociated dislocations in FCC materials is known to be complex: Observations of climb under HVEM irradiation in CuAl suggest that it, proceeds via the nucleation of interstitial loops directly onto individual partials. In silver, however, dissociated dislocations appear to constrict at an early stage in the irradiation, and dense vacancy cluster damage is seen to form in their vicinity. This thesis presents results and analysis of a study aimed at the determination of the interaction of HVEM generated interstitials and vacancies with pre-existing dislocations in a range of Fe-17Cr-Ni ternary alloys (with the nickel content varying between 15 and 40%). Two quaternary alloys (Fe-15%Ni-17%Cr-l%Si and Fe-15%Ni-17%Cr-2%Mo) arc also studied. As with earlier studies in CuAl and Ag, pre-existing dislocations in a (111) orientated foil were first characterized at subthreshold voltages employing the weak-becim technique, then irradiated with IMeV electrons at temperatures in the range 400-430°C and finally returned to the low voltage microscope for postirradiation characterization of the observed damage. Analysis of the post-irradiation microstructures indicates that interstitial climb only occurs at particularly favourable sites, such as pre-existing jogs: For the ternary alloys, constrictions are removed along edge and mixed dislocations, whilst zig-zagging of screw and near-screw dislocations may also be attributable to jog climb. After the annihilation of constrictions evidence of climb is not seen and pipe diffusion is thought to be occurring. The precipitation of small clusters, many of which are identifiable as vacancy SFT, is reminiscent of observations in silver. The addition of silicon to the matrix apparently leads to the creation of favourable sites for interstitial climb, as evidenced by the formation of high densities of new jogs after irradiation. Loops are seen to precipitate close to dislocations in the Mo-doped material. The origin of these loops is unclear at this stage. The relevance of the results to the phenomenon of void swelling is discussed.